1985
DOI: 10.1021/ma00154a036
|View full text |Cite
|
Sign up to set email alerts
|

Gel permeation chromatography of poly(N-vinyl-3,6-dibromocarbazole). Universal calibration, nonexclusion effects, and incompatibility

Abstract: Nonexclusion effects in the GPC of poly(N-vinyl-3,6-dibromocarbazole) ) in tetrahydrofuran, at 25 "C, using cross-linked polystyrene (PS) as the gel phase, are analyzed by use of the universal calibration method. The first point in order to determine such nonexclusion effects is to use values for the hydrodynamic volume and the elution volume truly representative of the samples. We show that an adequate set of average magnitudes is the weight-average intrinsic viscosity of the sample, the viscosity-average m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…A similar equation differing only in the two last terms has already been derived by Barrales-Rienda et al [39] and Tejero et al [40] Chromatographic evaluation of K p In size exclusion chromatography (SEC) on organic packings, the universal calibration concept [41] is well established for different polymers and solvents providing that the solvents are good for the polymers. However, when polymers are eluted in poor or "theta" solvents, solute-gel interactions become important and secondary mechanisms appear.…”
Section: )‚ and (Qg T /Qb 3 )99mentioning
confidence: 87%
See 2 more Smart Citations
“…A similar equation differing only in the two last terms has already been derived by Barrales-Rienda et al [39] and Tejero et al [40] Chromatographic evaluation of K p In size exclusion chromatography (SEC) on organic packings, the universal calibration concept [41] is well established for different polymers and solvents providing that the solvents are good for the polymers. However, when polymers are eluted in poor or "theta" solvents, solute-gel interactions become important and secondary mechanisms appear.…”
Section: )‚ and (Qg T /Qb 3 )99mentioning
confidence: 87%
“…On the contrary, due to the incompatibility between polymeric solute and gel the V e values are shifted towards smaller retention volumes. [39] Therefore, a theoretical expression for the distribution coefficient of the solute between the solvent and the gel, K p , has been previously derived. [39,40] In this paper we present a more extended theoretical procedure to evaluate K p from chromatographic measurements.…”
Section: )‚ and (Qg T /Qb 3 )99mentioning
confidence: 99%
See 1 more Smart Citation
“…1 values with hydrodynamic size are related to polymer -gel adsorption, [7,33] whereas K p , 1 decreasing values with rising size suggest repulsions between polymer and gel. (9), the corresponding K p coefficients for all the systems under study (values not shown).…”
Section: Size-exclusion Chromatography In Single and Mixed Eluents 253mentioning
confidence: 99%
“…2a) or CHCl 3 (Fig. The magnitude of these shifts must be a function of polymer size, through the K p dependence on molar mass, [7,33] that can result in different "shapes" of the log M[h] vs. V e plots. The above findings can also be explained through thermodynamic considerations.…”
Section: Size-exclusion Chromatography In Single and Mixed Eluents 253mentioning
confidence: 99%